Public health reform and health promotion in Canada. (June 2014) - Kirk, Megan; Tomm-Bonde, Laura; Schreiber, Rita
More than 25 years have passed since the release of the Ottawa Charter for Health Promotion. This document represented a substantial contribution to public health in its emphasis on the economic, legal, political and cultural factors that influence health. With public health renewal underway across Canada, and despite overwhelming support in the public health community for the Ottawa Charter, how much its principles will be included in the renewal process remains unclear. In this paper, we present the historical understanding of health promotion in Canada, namely highlighting the contributions from the Lalonde Report, Alma Ata Declaration, the Ottawa Charter for Health Promotion and the more recent population health movement. We discuss public health renewal, using the province of British Columbia in Canada as an example. We identify the potential threats to health promotion in public health renewal as it unfolds.